1-D transient numerical model of a regenerator in a novel sub Kelvin Active Magnetic Regenerative Refrigerator. (March 2016) - Jahromi, Amir E.; Miller, Franklin K.
Highlights: A sub-Kelvin AMRR that uses a 3He–4He mixture is modeled. A 1D transient numerical model is developed and used as a design tool. The model is used to design an AMRR capable of removing 2.5 mW at 750 mK at cyclic steady state. Abstract: A sub Kelvin Active Magnetic Regenerative Refrigerator (AMRR) is being developed at the University of Wisconsin – Madison. This AMRR consists of two circulators, two regenerators, one superleak, one cold heat exchanger, and two warm heat exchangers. The circulators are novel non-moving part pumps that reciprocate a superfluid mixture of 4 He– 3 He in the system. Heat from the mixture is removed within the two regenerators of this tandem system. An accurate model of the regenerators in this AMRR is necessary in order to predict the performance of these components, which in turn helps predicting the overall performance of the AMRR system. This work presents modeling methodology along with results from a 1-D transient numerical model of the regenerators of an AMRR capable of removing 2.5 mW at 850 mK at cyclic steady state.